2011
DOI: 10.1111/j.1750-3841.2010.02030.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sauerkraut Production with Probiotic Strain Lactobacillus plantarum L4 and Leuconostoc mesenteroides LMG 7954

Abstract: The results of this research could be applied in the production of fermented cabbage heads with added functional (probiotic) value and with lower NaCl concentration with expected shortened fermentation time. This could not only be of economic but also of ecological importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 22 publications
1
49
0
2
Order By: Relevance
“…These foods have the potential to promote health in ways not anticipated by traditional nutritional science (Beganović et al, 2011). Modern consumers are showing continuously a remarkable interest in functional foods with more emphasis in recent times on probiotic types of products.…”
Section: Introductionmentioning
confidence: 99%
“…These foods have the potential to promote health in ways not anticipated by traditional nutritional science (Beganović et al, 2011). Modern consumers are showing continuously a remarkable interest in functional foods with more emphasis in recent times on probiotic types of products.…”
Section: Introductionmentioning
confidence: 99%
“…SP1 significantly accelerated the fish sauce fermentation. Beganovié et al (2011) investigated the effect of probiotic strain Lactobaciilus plantarum L4 and Leuconostoc mesenteroides LMG 7954 addition on the production of sauerkraut. Results showed that the addition of both strains lowered the NaCl concentration from 4.0% to 2.5% (w/v), accelerated the fermentation process by 14 d and improved the product quality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the long period of fermentation also limited the development of CHCP industries. The use of starter culture has been reported to improve the quality of many fermented foods as well as shorten the fermentation process (Beganovié et al, 2011; C. Wu et al buffer and plated on to a sterile MRS (Oxoid) agar containing 1.5% CaCO 3 (w/v), 12% NaCl (w/v). This was subjected to incubation at 30℃ for 48 − 96 h, and the colonies that exhibited clear zone on the plates were individually picked and streaked on MRS agar containing 12% NaCl (w/v) and 1.5% (w/v) CaCO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…mesenteroides as a potential probiotic microorganism are rare in the literature. One of these studies was conducted recently by Beganovic and coworkers (80). The probiotic strains Lactobacillus plantarum L4 and Lc.…”
mentioning
confidence: 98%